Light-fueled transient supramolecular assemblies in water as fluorescence modulators - Chen, Xu-Man; Hou, Xiao-Fang; Bisoyi, Hari Krishna; Feng, Wei-Jie; Cao, Qin; Huang, Shuai; Yang, Hong; Chen, Dongzhong; Li, Quan (Nature communications, 2021)
Dissipative self-assembly, which requires a continuous supply of fuel to maintain the assembled states far from equilibrium, is the foundation of biological systems. Among a variety of fuels, light, the original fuel of natural dissipative self-assembly, is fundamentally important but remains a challenge to introduce into artificial dissipative self-assemblies. Here, we report an artificial dissipative self-assembly system that is constructed from light-induced amphiphiles. Such dissipative supramolecular assembly is easily performed using protonated sulfonato-merocyanine and chitosan based molecular and macromolecular components in water. Light irradiation induces the assembly of supramolecular nanoparticles, which spontaneously disassemble in the dark due to thermal back relaxation of the molecular switch. Owing to the presence of light-induced amphiphiles and the thermal dissociation mechanism, the lifetimes of these transient supramolecular nanoparticles are highly sensitive to temperature and light power and range from several minutes to hours. By incorporating various fluorophores into transient supramolecular nanoparticles, the processes of aggregation-induced emission and aggregation-caused quenching, along with periodic variations in fluorescent color over time, have been demonstrated. Transient supramolecular assemblies, which act as fluorescence modulators, can also function in human hepatocellular cancer cells. Dissipative self-assembly, which requires a continuous supply of fuel to maintain the assembled states far from equilibrium, is the foundation of biological systems but it remains a challenge to introduce light as fuel into artificial dissipative self-assemblies. Here, the authors report an artificial dissipative self-assembly system that is constructed from light-induced amphiphiles.